Targeted disruption of the BCR-ABL fusion gene by Cas9/dual-sgRNA inhibits proliferation and induces apoptosis in chronic myeloid leukemia cells - Zeng Jianling; Liang Xinquan; Duan Lili; Tan Fenghua; Chen Liujie; Qu Jiayao; Li Jia; Li Kai; Luo Dixian; Hu Zheng (Acta Biochimica et Biophysica Sinica, 2024)
The BCR-ABL fusion gene, formed by the fusion of the breakpoint cluster region protein (BCR) and the Abl Oncogene 1, Receptor Tyrosine Kinase (ABL) genes, encodes the BCR-ABL oncoprotein, which plays a crucial role in leukemogenesis. Current therapies have limited efficacy in patients with chronic myeloid leukemia (CML) because of drug resistance or disease relapse. Identification of novel strategies to treat CML is essential. This study aims to explore the efficiency of novel CRISPR-associated protein 9 (Cas9)/dual-single guide RNA (sgRNA)-mediated disruption of the BCR-ABL fusion gene by targeting BCR and cABL introns. A co-expression vector for Cas9 green fluorescent protein (GFP)/dual-BA-sgRNA targeting BCR and cABL introns is constructed to produce lentivirus to affect BCR-ABL expression in CML cells. The effects of dual-sgRNA virus-mediated disruption of BCR-ABL are analyzed via the use of a genomic sequence and at the protein expression level. Cell proliferation, cell clonogenic ability, and cell apoptosis are assessed after dual sgRNA virus infection, and phosphorylated BCR-ABL and its downstream signaling molecules are detected. These effects are further confirmed in a CML mouse model via tail vein injection of Cas9-GFP/dual-BA-sgRNA virus-infected cells and in primary cells isolated from patients with CML. Cas9-GFP/dual-BA-sgRNA efficiently disrupts BCR-ABL at the genomic sequence and gene expression levels in leukemia cells, leading to blockade of the BCR-ABL tyrosine kinase signaling pathway and disruption of its downstream molecules, followed by cell proliferation inhibition and cell apoptosis induction. This method prolongs the lifespan of CML model mice. Furthermore, the effect is confirmed in primary cells derived from patients with CML.